In pursuit of excellence - How to win in sport and life through mental training - Orlick, T. (Human Kinetics, 2008)
Author Terry Orlick, an internationally acclaimed sport psychologist, has helped hundreds of Olympic and professional athletes maximise their performances and achieve their goals. In this fourth edition, Orlick provides new insights and a powerful step-by-step plan for the reader to develop their own personal path to excellence. The reader will learn to focus for excellence and high-quality living. Through this book, the reader will gain a more positive outlook, a more focused commitment, better ways of dealing with distractions and strategies for overcoming obstacles. This new fourth edition guides readers to achieve greater personal and professional satisfaction and discover better ways to work with team-mates, respond more effectively to coaching and become more self-directed in thoughts and actions. Both practical and inspirational "In Pursuit of Excellence" is a guide to daily living and motivation as well as a road map to long-term achievement.